Basaloid carcinoma of the prostate: A literature review with case report - Jeffrey Tuan; Hardev Pandha; Cathy Corbishley; Vincent Khoo (Indian Journal of Urology, 2012)
Basal cell carcinoma of the prostate (BCP) is a neoplasm composed of prostatic basal cells. There are only a few publications outlining the diagnosis, treatment, prognosis and outcome for BCP. Traditionally surgery has been used but these tumors also respond to concomitant chemo-radiotherapy. Using a BCP case report treated with radical chemo-radiotherapy from a chemotherapy regimen used in anal cancers, we propose an alternative management to the traditional options of radical surgery and radical radiotherapy.